Neither secular state nor laical republic? Legal position of religious communities in communist Yugoslavia – legal framework analysis - Božić, Marko D (Pravni zapisi, 2019)
The paper is a contribution to a scholarly debate on the controversial secular nature of the communist state. It aims to challenge a presumed affiliation of Yugoslav communist model of church and state separation to French laical approach through examination of legal status of religious communities in Yugoslavia between 1946 and 1991. Methodologically restricted to a normative analysis of basic legal framework, the paper particularly sheds light on religious liberty, religious education and public funding of religious communities. It detects signs of evolution in official legal politics towards religion and emphasizes differences between the eight parallel Yugoslav legal systems that existed since the mid-seventies. Strictly analytical, the achieved results justify plausibility of starting presumption without pretending to give a final answer. As such, the paper presents a groundwork for further enquiries that would combine its normative findings with relevant sociological and historical data. Key words: secularism, laicism, communism, Yugoslavia, legal status of religious communities, religious liberty, state and church relation.